HUBUNGAN KECEMASAN DAN STRATEGI KOPING DENGAN RESILIENSI PASIEN KANKER PAYUDARADI RUMAH X,JAKARTA - Faranciska Sando Sinaga (2023)
Breast cancer is one of the diseases that can cause death. Cancer has an impact on many aspects of the lives of sufferers, both physically, psychologically and spiritually. The purpose of this study was to determine the relationship between anxiety and coping strategies with the resilience of breast cancer patients at "X" Hospital Jakarta. This study used a quantitative research design with a cross sectional approach. The sample in the study amounted to 40 respondents using the technique. accidental sampling. Anxiety level was measured using the Zung Self-Rating Anxiety Scale (SAS/ZRAS) questionnaire, The Cancer Coping Questionnaire to measure coping and the Resilience Scale questionnaire to measure patient resilience. The data analysis used was univariate analysis with frequency distribution and bivariate analysis using the chi square test. The results showed that there was a relationship between anxiety and resilience with a p-value of 0.003 (p<0.05) and there was a relationship between coping strategies and resilience with a p-value of 0.002 (p<005). The results showed that there was a relationship between anxiety and coping strategies with the resilience of cancer patients. Nurses are expected to be able to provide education to breast cancer patients so that anxiety decreases and is able to form adaptive coping so as to form better resilience. Keywords: Anxiety, Breast Cancer, Coping Strategies, Resilience